ANALYZING THE EFFECTS OF PRODUCT QUALITY, PACKAGING, PROMOTIONAL OFFER, AVAILABILITY, AND VARIETY TOWARD BRAND LOYALTY OF “MIE SEDAAP” - Pangaribuan, Christian Haposan; Yandi, Muhammad; Ardiansyah, Muhril (Journal of Business And Entrepreneurship, 2018)
This research was motivated by business rivalry in instant noodle segment in Indonesia. From time to time, the business in this sector is getting tight therefore the company needs to create a new marketing strategy in order to keep the market share steady if not higher. For the past several years, most of the market shares of instant noodle business in Indonesia is led by Indomie. The objective of this study is to see which factor would affect the brand loyalty of one of Indomie’s competitors, Mie Sedaap. The purpose of this study is to analyze whether or not product quality, packaging, promotional offer, availability, and variety affecting brand loyalty. The questionnaires were distributed online to 164 college students of Sampoerna University. The data were analyzed in the form of quantitative analysis using validity test, reliability test, multicollinearity test, multiple correlation test, multiple regression test F-test and t-test. The study found out that availability and variety significantly affect the dependent variable. Keywords: brand loyalty, product quality, packaging, promotional offer, availability, variety Penelitian ini dilatarbelakangi oleh persaingan bisnis di segmen mie instan di Indonesia. Dari waktu ke waktu, bisnis di sektor ini semakin ketat sehingga perusahaan perlu membuat strategi pemasaran baru agar pangsa pasar tetap stabil jika tidak lebih tinggi. Selama beberapa tahun terakhir, sebagian besar pangsa pasar bisnis mie instan di Indonesia dipimpin oleh Indomie. Tujuan dari penelitian ini adalah untuk melihat faktor mana yang akan mempengaruhi loyalitas merek dari salah satu pesaing Indomie, Mie Sedaap. Tujuan dari penelitian ini adalah untuk menganalisis apakah kualitas produk, kemasan, penawaran promosi, ketersediaan, dan variasi mempengaruhi loyalitas merek. Kuesioner dibagikan secara online kepada 164 mahasiswa Universitas Sampoerna. Data dianalisis dalam bentuk kuantitatif menggunakan uji validitas, uji reliabilitas, uji multikolinieritas, uji korelasi ganda, uji regresi berganda F-test dan uji-t. Studi ini menemukan bahwa ketersediaan dan variasi secara signifikan mempengaruhi variabel dependen. Kata Kunci: loyalitas merek, kualitas produk, pengemasan, penawaran promosi, ketersediaan, variasi